2017
DOI: 10.18176/jiaci.0144
|View full text |Cite
|
Sign up to set email alerts
|

Role of Periostin in Uncontrolled Asthma in Children (DADO study)

Abstract: Background: Asthma is the most common chronic disease in children. Cases of severe asthma (SA) are underdiagnosed. Periostin is a biomarker for SA in adults, but its role in children is poorly understood. Objectives: The aims of the study were to estimate the percentage of cases of uncontrolled severe asthma (UcSA) in children with poorly controlled asthma and to evaluate the role of periostin as a biomarker. Materials and Methods: We performed an observational study in children aged 5 to 14 years with poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
1
6
1
1
Order By: Relevance
“…Lopez-Guisa and colleagues evaluated periostin levels in bronchial and nasal cells from asthmatic, non-asthmatic, atopic, and healthy children and found a significant increase in periostin levels in asthmatic children (3.7 times), as compared to the other groups (96). These results were confirmed in studies that showed a correlation between high levels of periostin in the serum with persistent or uncontrolled asthma in children (97, 98). In fact, clinical manifestations of asthma are considered to be very similar to bronchiolitis symptoms (123).…”
Section: Severity Prognosis In Hrsv Infectionsupporting
confidence: 63%
“…Lopez-Guisa and colleagues evaluated periostin levels in bronchial and nasal cells from asthmatic, non-asthmatic, atopic, and healthy children and found a significant increase in periostin levels in asthmatic children (3.7 times), as compared to the other groups (96). These results were confirmed in studies that showed a correlation between high levels of periostin in the serum with persistent or uncontrolled asthma in children (97, 98). In fact, clinical manifestations of asthma are considered to be very similar to bronchiolitis symptoms (123).…”
Section: Severity Prognosis In Hrsv Infectionsupporting
confidence: 63%
“…Therefore, it is considered that determining the level of serum periostin in children aged ≥ 6 years may be helpful in the diagnosis of asthma. Conversely, Habernau Menaet al 21 have shown that children with severe uncontrolled asthma have lower periostin levels than children with severe controlled asthma. Therefore, it is unclear whether periostin measurements in developing children with asthma are useful.…”
Section: Discussionmentioning
confidence: 95%
“…They studied 28 children with controlled persistent asthma and 27 healthy children (6–16 years) and assessed utility of serum periostin levels in diagnosing pediatric asthma, as they detected periostin values equivalent to conventional biomarkers, confirming the utility of serum periostin levels in diagnosing asthma in children. [ 73 ] Habernau et al [ 74 ] measured serum periostin in a group of children (5–14 years old) with uncontrolled asthma and without correct treatment, and they found higher periostin levels (average 900 ng dl –1 ) compared to previous studies published in children with controlled asthma and with adequate treatment following clinical guidelines.…”
Section: Other Biomarkersmentioning
confidence: 99%